Industrial Capital Intensity and Comparative Advantages Dynamism of Indonesian Export Products - Ni Putu Wiwin Setyari; Tri Widodo; Muhammad Edhie Purnawan (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2015)
The development of new trade theory which incorporates the interaction between trade and international capital flows indicates if the possibility of changes in a country's comparative advantage due to the opening of international capital flows. International capi tal flows allow for changes in the industrial structure of a country depends on the composition of the products produced in that coun try. More capital-intensive types of products produced by a country, the greater the need for capital and the higher marginal rate of capital that can be given to attract greater international capital flows. Therefore, a comparative advantage should be seen as dynamic rather than static. As a country with large population, Indonesia tends to specialize in labor -intensive products. The other hand, efforts to attract foreign direct investment are very intensively conducted. The estimation results indicate if there was a shift in the pattern of industrial specialization Indonesia, from labor –intensive tends toward capital intensive.